PEMBERDAYAAN EKONOMI PEREMPUAN MELALUI EDUKASI KONSEP EKONOMI KREATIF INDUSTRI RUMAH TANGGA DI KECAMATAN BINJAI KOTA - Dewi Mahrani Rangkuty; Mesra B; Aldi Agustino (Jurnal Pasca Dharma Pengabdian Masyarakat, 2020)
Today's digital Era demands creativity to continue innovating in improving women's productivity, especially on fulfilling daily household consumption needs. This is closely related to women's empowerment because as a partner of the household can participate in increasing household income. The creativity of ideas in innovating produces a product that adds value to the economy is called the creative economy. The goal of devotion to this society enhances understanding, knowledge, and insight to women the importance of the creative economy in increasing family income. Implementation of a creative economy in the early stages, can not be done only on one person, therefore, it need support from several parties so effective when the formed a business group. This is what is a tangible form of this devotion activity. The dedication partners consist of RMOL Sumut, PKK women, IWAPI women, and Genre communities in the Binjai City district. Method of devotion done with the lecture, discussion question/answer problem, and the final stage is an alternative solution offered. From this community devotion activity, all participants were enthusiastic about the deepening of knowledge and insight into the concept of creative economics. And there were 20 business groups in which each group consisted of 5 people. So much devotion activities are important to continue to be implemented continually to increase household income to prosperity.